Predictors of inadequate bowel preparation for colonoscopy: a systematic review and meta-analysis. Issue 8 (August 2018) - Mahmood, Sultan; Farooqui, Samid M.; Madhoun, Mohammad F.
Abstract : The aim of this study was to investigate factors contributing to poor bowel preparation in patients undergoing colonoscopy procedures. We used a reproducible search strategy to identify studies, searching 10 medical databases, including PubMed, Ovid, Medline, and Cochrane Library Database for reports published between 2000 and 2016. Fully published studies, evaluating risk factors for inadequate bowel preparation, were included. Two reviewers independently scored the identified studies for methodology and abstracted pertinent data. Pooling was conducted with both fixed-effects and random-effects models; results were presented from the random effects model when heterogeneity was significant. Odds ratios (OR) estimates with 95% confidence interval were calculated. Heterogeneity was assessed by I 2 statistics. Twenty-four studies with a total of 49 868 patients met the inclusion criteria. Age (OR: −1.20), male sex (OR: 0.85), inpatient status (OR: 0.57), diabetes mellitus (OR: 0.58), hypertension (OR: 0.58), cirrhosis (OR: 0.49), narcotic use (OR: 0.59), constipation (OR: 0.61), stroke (OR; 0.51), and tricyclic antidepressant (TCA) use (0.51), were associated with inadequate bowel preparation. In our sensitivity analysis comparing Western and Asian countries, we found that diabetes, cirrhosis, male sex, history of stroke and TCA use were stronger risk factors for inadequate bowel preparation in Western countries than in Asian countries. We also found that history of stroke, TCA use, and race were risk factors for inadequate bowel preparation in patients receiving conventional bowel preparation compared with those receiving split-dose bowel preparation. Multiple risk factors affect the quality of bowel preparation and specific risk factors can be intervened upon, in different populations, to optimize preparation.